2021
DOI: 10.1371/journal.pone.0246887
|View full text |Cite
|
Sign up to set email alerts
|

Effects of occupational balance on subjective health, quality of life, and health-related variables in community-dwelling older adults: A structural equation modeling approach

Abstract: Occupational balance is an important variable associated with health and quality of life. This study aimed to investigate the influence of occupational balance on health, quality of life, and other health-related variables using structural equation modeling. We analyzed data from 208 adults over 55 years old. Mean age of the participants was 70.21 years (SD 7.22). The research model for analysis was based on the results of previous studies addressing occupational balance and related variables such as stress, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 35 publications
1
30
0
2
Order By: Relevance
“…There is evidence that informal caregiving leads to limited occupational balance [ 29 , 31 , 33 ] and a need for interventions to support informal caregivers’ occupational balance [ 33 , 34 ]. Furthermore, occupational balance was found to be associated with health, quality of life and well-being [ 32 , 35 38 ]. For example, Park et al reported direct effects of occupational balance on health, well-being and quality of life [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that informal caregiving leads to limited occupational balance [ 29 , 31 , 33 ] and a need for interventions to support informal caregivers’ occupational balance [ 33 , 34 ]. Furthermore, occupational balance was found to be associated with health, quality of life and well-being [ 32 , 35 38 ]. For example, Park et al reported direct effects of occupational balance on health, well-being and quality of life [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…promovem maior satisfação e adesão dos pacientes e, a longo prazo, são economicamente mais atrativos (DANILOV et al, 2018). (JONGEN et al, 2017;PARK et al, 2021). Assim, a proposta "Desafio de talentos" contribuiu para uma participação mais diversificada dos pacientes com dor crônica e ofereceu um espaço virtual para compartilharem habilidades e competências significativas por meio de redes sociais.…”
Section: Webconferências E Atuação Interdisciplinar No Cuidado E Assistência Ao Paciente Com Dor Crônicaunclassified
“…Occupational therapy practice is based on the fundamental assumption that meaningful occupations play a key role in achieving and maintaining health and wellbeing by facilitating personal engagement and accomplishment [ 1 ]. This practice framework rests largely on the fact that occupational performance should involve an occupational balance (OB), i.e., a sense of harmony between occupations, becoming a necessary condition to ensure that occupations properly perform a process for obtaining health and wellness [ 2 ]. From an occupational perspective of health, it should be noted that there is a variety of risk factors that can affect the right use, choice, opportunity, or balance in an occupation, thereby resulting in occupational dysfunction, which may also involve other negative consequences such as occupational deprivation, occupational alienation, or occupational imbalance [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, several studies have provided some evidence that OB may be a major occupational determinant of health outcomes. On a positive note, the main research findings have suggested that OB is perceived as a good proxy of self-rated health [ 2 , 4 , 5 , 6 , 7 , 8 ] and related to life satisfaction [ 2 , 4 , 5 , 6 ] and health-related quality of life [ 2 , 9 ]. On the other hand, some studies have reported that occupational imbalance is linked to perceived stress [ 2 , 5 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation